Correlations of Aldehyde dehydrogenase-1 (ALDH1) expression with traditional prognostic parameters and different molecular subtypes of breast carcinoma - Sarkar, Piyabi; Basu, Keya; Sarkar, Pubali; Chatterjee, Uttara; Mukhopadhyay, Madhumita; Choudhuri, Manoj Kumar; Srakar, Diptendra Kumar (Medicine and Pharmacy Reports, 2018)
Background and aim. Breast cancer, a heterogeneous disease, is the most common cause of cancer-related death in women worldwide. Despite considerable developments in treatment modalities, a subset of patients with advanced-stage breast carcinoma display poor prognosis. Breast cancer heterogeneity and risk of recurrence could be explained with the help of cancer stem cell hypothesis. Stem cells have the capacity to self-renew and differentiate into multiple cell types. Aldehyde dehydrogenase-1 (ALDH1), an enzyme responsible for the oxidation of intracellular aldehydes, contributes to normal and tumor stem cell differentiation. Invasion and metastasis in breast cancer are found to be mediated by a subpopulation of tumor cells which exhibit stem cell-like features and express ALDH1. The aim was to document ALDH1 expression in breast carcinoma and find its association with other clinico-pathologic prognostic parameters. Study design. This was a cross-sectional observational study. Methods. A total of 62 patients with breast carcinoma undergoing mastectomy were included in this study. The tumors were classified into molecular subtypes by assessing immunohistochemical (IHC) expression of ER, PgR, HER2 and Ki-67 according to St. Gallen Consensus Conference 2013. ALDH1 expression was studied by IHC and correlated with clinicoathological parameters. Statistical analysis. Statistical analysis was done using Graph Pad software (Prism 5 version) for Windows 7. A p-value <0.05 was considered statistically significant. Results and analysis. Out of 62 tumors, 35 tumors (56.4%) showed ALDH1 positivity. ALDH1 expression was significantly associated with larger size, lymph node involvement, higher grade, higher stage and HER2+ or triple negative tumors. Conclusion. This study suggests that ALDH1 expression is associated with poor prognostic parameters and aggressive tumor behavior. Larger population-based prospective trials on Indian patients are required to validate these results.